NGAMBOL: UNGKAPAN KEMARAHAN MASYARAKAT MELAYU PONTIANAK KALIMANTAN BARAT - Syarifah Lubna (tuahtalino, 2020)
There are five expression in the society of Pontianak Malay Kalimantan Barat in expressing their anger, that are: nyumpah, nyeranah, beleter, pendek tongkeng, and ngambol. These anger expressions are different in their daily application. Ngambol is ironic in anger expression character since it is not express direct anger but agreeing their speaking partner with special facial expression and voice tone to show disagreement of the spoken statement. Ngambol becomes the focus of this research. Qualitatively, ngambol is described and become the aim of the research. 100 respondents selected randomly from the total population of the society of Pontianak Malay Kalimantan Barat to be the sample of the research.  This study applied descriptive statistics. The data collected and disseminated through questionnaires and analyzed through tabulation of statistical product and service solution (SPSS) based on the Likert scale which are: strongly disagree (1), disagree (2), doubtful (3), agree (4), and strongly agree (5). Based on the data, it could be concluded that 36% society of Pontianak Malay respondents agree even strongly agree to express their anger through ngambol in their closest social environment.